Effects of prone and supine position on cerebral blood flow in preterm infants. - Bembich, Stefano; Oretti, Chiara; Travan, Laura; Clarici, Andrea; Massaccesi, Stefano; Demarini, Sergio (J Pediatr, 2012)
We evaluated the effect of prone and supine position on cerebral blood flow (CBF) in stable preterm infants. CBF, PO(2), and PCO(2) were measured in the two positions. Peripheral oxygenation increased and CBF decreased in prone position. We speculate that CBF autoregulation may compensate for increased peripheral oxygenation, by decreasing CBF.
Keywords: Cerebrovascular Circulation; Female; Humans; Infant, Newborn; Infant, Premature; Male; Prone Position; Regional Blood Flow; Supine Position